Detecting Vegetation Losses in Tumpat Shrimp Farming Area using Remote Sensing Technique - Shaharlina Abd Rasid (2018)
The conversion of mangrove forest to aquaculture activities leads to a destruction of flora and fauna that utilize the mangrove areas as habitat, shelter and breeding place. Pulau Terendak, Tumpat, Kelantan located at latitude of 6°12'35.4" N and longitude of 102°11'4.8" E is one of the area occupied for shrimp farming activity in Tumpat district. In this study, the current status and the total areas of the converted land from shrimp farms was analyzed using image from remote sensing. The Landsat data of 1989 and 2017 were analyzed to see the dynamic changes of vegetation losses at the study area. The percentage of the vegetation losses at the area were calculated by classifying the image using a supervised image classification technique. The percentage of vegetation cover decreased between years 1989 to 2017. In 1989 the 25.0 hectare of the area covered by dense vegetation, while in 2017, it decreased to 20.13 ha. The decreased of vegetation cover was due to the conversion of the mangrove area to the shrimp farm. The establishment of the shrimp farm had caused water coverage area increased when the natural mangrove area in Pulau Terendak was converted to shrimp farms by the locals. The standing trees were cut off and the construction of the shrimp farm started to take place and due to the growing small tress in the abandoned shrimp farm.